(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
This paper deal with shock and vibration insulators, which usually are performed from the elastomeric (rubber-like) materials. Elastomeric materials give many engineering advantages due to their capability of absorbing input energy much better than engineering materials, high elasticity, good dynamic properties, low volume compressibility, a linear relationship between stress and strain up to strain of 15% ÷ 20%, resistance to aggressive environmental factors. Elastomeric materials are widely used in machine building, shipbuilding, civil engineering, aviation and aerospace as compensation devices, vibration dampers, shock absorbers. Laminated elastomers, consisting of interleaved thin layers of elastomer and rigid reinforcing layers are also successfully used as bearing, joints, dampers, compensating devices, shock-absorbers. Such structures have many advantages: ability to endure high stress (>200 MPa), ease of maintenance, non- necessity for lubrication, vibration and noise reduction, ability to work in a very dirty, dusty, abrasive environment. The disadvantage of elastomeric material are aging, i.e. changing its properties over time. In this paper the influence of aging of elastomeric materials on the damping properties of shock absorbers is considered based on the mechanical models of elastomers - Maxwell and Burgers modes. Fatigue endurance, i.e. the ability to withstand mechanical actions for a long time is studied based on experiments on dynamic shear with laminated rubber-metal structures. The experiments show that such structures have a very high fatigue life - up to 100 million cycles.